2019
DOI: 10.3389/fpsyg.2019.02075
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Traditional Chinese Mind-Body Exercise (Baduanjin) and Brisk Walking on the Dorsal Attention Network in Older Adults With Mild Cognitive Impairment

Abstract: A growing number of studies have shown that mind-body exercise is beneficial to cognitive function, especially memory, in elderly MCI patients. However, few studies have explored the effect of mind-body exercise on the attention of MCI population. We recruited 69 participants and divided them equally into Baduanjin, brisk walking (BWK) exercise or usual physical activity (UAP) control groups. The two exercise groups performed 60 min of exercise three times per week for 24 weeks. All subjects underwent whole-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 42 publications
(45 reference statements)
0
50
0
1
Order By: Relevance
“…Of the 47 eligible studies, 8 evidently did not include controls [ 7 , 28 , 38 , 39 , 48 , 58 60 ], and 5 used more than two control groups [ 21 24 , 49 ]. Three studies used walking as a control [ 34 , 42 , 54 ], and other control measures used in single studies were muscle relaxation training [ 30 ], reading [ 6 ], physical therapy [ 19 ], and an aerobic exercise [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 47 eligible studies, 8 evidently did not include controls [ 7 , 28 , 38 , 39 , 48 , 58 60 ], and 5 used more than two control groups [ 21 24 , 49 ]. Three studies used walking as a control [ 34 , 42 , 54 ], and other control measures used in single studies were muscle relaxation training [ 30 ], reading [ 6 ], physical therapy [ 19 ], and an aerobic exercise [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Some studies recently reported that the Baduanjin exercise was beneficial in maintaining or even improving both global cognitive function and specific domains of cognition including memory processing speed, executive function, attention or verbal learning and memory in older adults with or without cognitive impairment. [12][13][14] Therefore, Baduanjin training may improve cognition in stroke survivors, but no randomized controlled trials have been published to investigate the effect of Baduanjin training on cognition among stroke survivors. Consequently, the primary aim of this study was to evaluate systematically the effect of a 24-week Baduanjin exercise programme on the cognitive function including globe cognitive function and specific domain of cognition, such as memory, attention, execution, processing speed and visuospatial ability in stroke patients with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 16 randomized controlled trials with 1054 participants were considered to be eligible for analysis. 13 –28 Three of these studies were not included in the meta-analysis. One study 13 had high heterogeneity (Montreal Cognitive Assessment-BJ), and some of its data (auditory verbal learning test) could not be merged.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 studies 15,20 –28 with 709 patients assessed the Montreal Cognitive Assessment-BJ scores at 2, 3, and 4 months of treatment. No significant heterogeneity was found among these studies ( P > 0.05, I 2 < 50%), so the fixed-effects model was used.…”
Section: Cognitive Function Outcomesmentioning
confidence: 99%